Atypical antipsychotics:: analysis of adverse events - Ferreira, Claudia Aparecida Avelar; Santos, Isabelle Cristina de Oliveira; Guimarães, Hairton Ayres Azevedo; Azevedo, Maisa Aparecida Guatimosim; Souza, Waldirce Inêz de (Revista Gestão & Saúde, 2015)
The aim was to identify adverse events arising from the continued use of atypical antipsychotics through cohort and case control studies, carried out on a worldwide level, in the period from 2013 and 2014. Method: A literature review was performed from an exploratory study seeking cohort and case control studies about atypical antipsychotics with bibliometrics application according to Bradford’s Law. Results: The study resulted in 291 surveyed articles, of which 18 were selected and analyzed. Conclusion: the main findings were cardiovascular risk, QT interval prolongation, diabetes, increased body mass index, extrapyramidal effects.